Imagi(ni)ng Urban Transformation in Post-Détente Havana - Heiskanen Benita (Filmiverkko ry, 2022)
This article probes the visual implications of urban transformation in Havana in the aftermath of the re-establishment of diplomatic relations between Cuba and the United States on December 17, 2014 (D17). The rapprochement provides a new geopolitical context to study the ways in which binational policy-making and multinational financial investments are reflected visually in Cuba’s capital city. Drawing on fieldwork conducted in Havana in June–July 2015, as well as online sources, the article focuses on parts of urban Havana, where transformations are underway. By situating the research in different urban locations, the discussion emphasizes both the significance of visual-spatial power relations and Cubans as a heterogeneous community, whose members have multiple ways to negotiate, interact with, and represent ongoing societal changes impacting their lives.
The article poses the following questions: How do various actors in Havana imagine urban transformation in the détente context? How do their differing viewpoints assume visual expression in various parts of the city? What kinds of tensions can be evidenced from official and unofficial visual statements? Urban transformation does not solely entail policy-making, but necessarily comprises a complex web of issues combining financial investments, visual statements, and personal experiences. This article’s visual-spatial framework delineates societal change in Cuba as a complex nexus that intertwines everyday experiences, visual expressions, and formal and informal modes of communication. In so doing, it captures the social realities of residents of Havana in their everyday surroundings, exposing multiple linkages between policy-making and online and grassroots visual culture.